Exploring the Phytochemical Compositions, Antioxidant Activity, and Nutritional Potentials of Edible and Medicinal Mushrooms - Mohammed Al Qutaibi; Suresh R. Kagne (International Journal of Microbiology)
Mushrooms are a valuable source of food and medicine that have been used for centuries in various cultures. They contain a variety of phytochemicals, such as terpenoids and polysaccharides, that exhibit diverse biological activities, such as antioxidant, anti-inflammatory, anticancer, antimicrobial, immunomodulatory, and antidiabetic effects. However, mushroom’s phytochemical composition and bioactivity vary depending on their species, cultivation conditions, processing methods, and extraction techniques. Therefore, using reliable analytical methods and standardized protocols is important for systematically evaluating the quality and quantity of mushroom phytochemicals and their therapeutic potential. This review provides a bibliometric analysis of the recent literature on biological activities, highlights trends in the field, and highlights the countries and journals with the highest contribution. It also discusses the nutritional value of the total content of phenolic and other phytochemicals in some species of mushrooms.